Ligand Migration from Cluster to Support: A Crucial Factor for Catalysis by Thiolate‐protected Gold Clusters. Issue 23 (7th December 2018) - Zhang, Bei; Sels, Annelies; Salassa, Giovanni; Pollitt, Stephan; Truttmann, Vera; Rameshan, Christoph; Llorca, Jordi; Olszewski, Wojciech; Rupprechter, Günther; Bürgi, Thomas; Barrabés, Noelia
Abstract: The front cover artwork for issue 23/2018 is provided by an international group of scientists from the University of Geneva (Switzerland), the Technical University of Vienna (Austria), the Universitat Politècnica de Catalunya and ALBA Synchrotron Light Facility (Spain), and the University of Bialystok (Poland). The image shows the thiol ligand migration from the gold nanocluster to the surface once it has been supported, forming sulfur oxide species. See the Communication itself at https://doi.org/10.1002/cctc.201801474 . Abstract : "The transformation of the thiol ligand to SOx species on the support plays an important role and should not be neglected when interpreting catalytic data." This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201801474 .